U.S. Air Force by the numbers - M B Simons, Lisa (North Mankato, Minnesota Capstone Press, 2014)
Describes aspects of the U.S. Air Force using numbers, stats, and infographics
A gift from book Africa
Industries
1 2 13 15
Keywords: Military art and science; United States -- Air Force